Disparity depth map layers representation for image view synthesis - Abd Manap, Nurulfajar; Soraghan, John J. (Penerbit Universiti, UTeM, 2014)
This paper presents a method that jointly performs stereo matching and inter-view interpolation to obtain the depth map and virtual view image. A novel view synthesis method based on depth map layers representation of the stereo image pairs is proposed. The main idea of this approach is to separate the depth map into several layers of depth based on the disparity distance of the corresponding points. The novel view synthesis can be interpolated independently to each layer of depth by masking the particular depth layer. The final novel view synthesis obtained with the entire layers flattens into a single layer. Since the image view synthesis is performed in separate layers, the extracted new virtual object can be superimposed onto another 3D scene. The method is useful to imply free viewpoint video application with a small number of camera configurations. Based on the experimental results, it shows that the algorithm improve the efficiency of finding the depth map and to synthesis the new virtual view images.